First operation of free-electron maser based on a combined two-mirror cavity based on 2D and 1D Bragg structures - Cross, A; Konoplev, I; He, W; McInnes, P; Phelps, A; Ronald, K; Whyte, C; Robertson, C; IEEE (2006)
We report the results of studies of operation of the coaxial FEM based on Mo-dimensional distributed feedback. The cavity formed with the novel Bragg structures have been used. The FEM output radiation is studied and output power is measured. © 2006 IEEE.